AI Companions Reduce Loneliness - De Freitas, Julian; Oğuz-Uğuralp, Zeliha; Uğuralp, Ahmet Kaan; Puntoni, Stefano (Journal of Consumer Research, 2026)
Abstract Chatbots are now able to engage in sophisticated conversations with consumers in the domain of relationships, providing a potential coping solution to widescale societal loneliness. Behavioral research provides little insight into whether these applications (apps) are effective at alleviating loneliness. We address this question by focusing on “artificial intelligence (AI) companions”: apps designed to provide consumers with synthetic interaction partners. Study 1 examines user reviews of AI companion apps and finds correlational evidence suggesting that these apps help alleviate loneliness. Study 2 finds that AI companions successfully alleviate loneliness on par only with interacting with another person and more than other activities such as watching YouTube videos. Moreover, consumers underestimate the degree to which AI companions improve their loneliness. Study 3 uses a longitudinal design and finds that an AI companion consistently provides momentary reductions in loneliness after use over the course of a week. Study 4 provides evidence that both the chatbots’ performance and, especially, whether it makes users feel heard, explain reductions in loneliness. Study 5 provides an additional robustness check for the loneliness-alleviating benefits of AI companions and shows that self-disclosure and distraction alone do not explain AI companions’ effectiveness.